Emotion and Motivation Consequences of Attributional Training During a Novel Physical Task. Issue 2 (3rd April 2022) - Simonton, Kelly L.; Garn, Alex C.
ABSTRACT: Purpose : Students' positive emotional experiences are an essential physical education outcome because they promote achievement-oriented cognition and behavior. The manner in which students attribute success and failure triggers emotional experiences. Students' beliefs that success is under their control are thought to be a precursor to positive emotions. Research on these relationships has mostly been observational; thus, experimental design was used to address this gap. The purpose of this study was to investigate the effects of attributional training (AT) on students' emotions and motivation toward a PE-related task. Method : Participants were female university students ( N  = 144; Mage = 20.92, SD = 2.13) recruited from Kinesiology courses. Participants were randomly assigned to one of the three experimental treatments (high AT = 46; low AT = 49; control = 49). Each treatment group received targeted control belief prompts, instruction, and feedback while learning a novel task. Data were collected on students' emotions and motivation before and after treatment. Results : Repeated measures analysis showed that participants receiving high AT increased enjoyment and reduced boredom over time compared to other groups. Feelings of anxiety trended down over time in all three groups while feelings of relief trended up. Free-choice activity did not show a significant group by time interaction. Conclusion : Our results show that AT can influence control beliefs in ways that increase students' enjoyment and reduce boredom in physical education tasks. Therefore, training physical education teachers to create a high AT learning environment appears to be a viable strategy for promoting adaptive emotions when students are learning novel tasks.